Menelusuri Labirin Peran Perempuan Dalam Pelayanan Gereja Yang Patriarki - Astrid Natasya; Hikman Sirait; Meriyana (Vox Dei: Jurnal Teologi dan Pastoral, 2024)
The role of women in church ministry has been a long topic, especially in the context of churches that still adhere to patriarchal structures. The patriarchal church still places women in certain tasks that are considered "traditional" or "appropriate" to gender stereotypes and limits women to certain areas of service. This study uses a descriptive qualitative approach. The results of this study show that the winding path of women in the ministry of patriarchal churches is more due to factors from within women, both in terms of emotional, intellectual and psychological aspects. Meanwhile, external factors are more about the negative stigma of patriarchal society that women should not lead men. These obstacles are a reality, but the church needs to guide women to overcome these weaknesses and at the same time enlighten men about the role of women in the ministry in this modern era. Through continuous guidance, women have great potential to develop and make a wide contribution to church ministry.